2012
DOI: 10.1111/j.1600-051x.2012.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peri‐implant diseases. A cross‐sectional study based on a private practice environment

Abstract: The prevalence of peri-implantitis in private practice patients enrolled in a periodontal maintenance programme was estimated to be between 12% and 22%. Almost 40% of the patients had mucositis. These prevalences are similar to those published in University environment samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
113
3
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 14 publications
9
113
3
10
Order By: Relevance
“…If not properly managed, it is a debilitating condition that results in loss of function and esthetics (Fransson et al, 2010). Recent studies and reviews (Zitzmann and Berglundh, 2008;Fransson et al, 2009;Albrektsson et al, 2012;Koldsland et al, 2010;Mir-Mari et al, 2012) reported that peri-implantitis occurred in 2.7% to 47.1% of implants. This wide range in prevalence rates can be attributed to the differences in study population, disease definition, and implant micro-and macrostructures.…”
Section: Introductionmentioning
confidence: 99%
“…If not properly managed, it is a debilitating condition that results in loss of function and esthetics (Fransson et al, 2010). Recent studies and reviews (Zitzmann and Berglundh, 2008;Fransson et al, 2009;Albrektsson et al, 2012;Koldsland et al, 2010;Mir-Mari et al, 2012) reported that peri-implantitis occurred in 2.7% to 47.1% of implants. This wide range in prevalence rates can be attributed to the differences in study population, disease definition, and implant micro-and macrostructures.…”
Section: Introductionmentioning
confidence: 99%
“…(40) peri-implant mukozitisli implantlara sahip 29 hastada yaptıkları çalışmada, mekanik tedaviye ek olarak %0,5'lik klorheksidin jelin 4 haftalık kullanımının tek başına mekanik tedaviye bir üstünlüğü olmadığı sonucuna varmışlardır. Öte yandan klorheksidinin farklı oran ve sıklıkta kullanımı, peri-implant mukozitis tedavisinde farklı sonuçlara yol açmaktadır (Resim 4) (15,39,41).…”
Section: Antimikrobiyal Tedaviunclassified
“…9 The diagnostic criteria for peri-implantitis was bone loss ≥ 2 threads with BOP or suppuration. Peri-implantitis was defined as the presence of inflamed mucosa with a positive BOP, PD ≥ 5 mm and cumulative bone loss of ≥ 2 mm and/or > 3 threads of the implant.…”
Section: Definition and Prevalencementioning
confidence: 99%